Implementasi Modifikasi Kompresi Run-Length Encoding pada Steganografi - Suwardiman Suwardiman; Fitri Bimantoro (Journal of Computer Science and Informatics Engineering (J-Cosine), 2020)
RLE is one of the methods to compress data, however it has disadvantages that the compressed data may become twice larger as the original size. Therefore, in this research RLE will be modified to solve the problem. In the experiment we tested 3 file format i.e. JPG, PNG and BMP. The testing on JPG and PNG shows that conventional RLE method is not able to compress all images because it obtained negative compression ratio with an average compression ratio about -97.4%, Meanwhile the compression with RLE modification shows that the all image successfully compress with an average compression ratio about 0.31%. The testing on BMP shows the conventional RLE method successfully compress 5 files out of 11 tested images with average compression ratio about -25.4%, Meanwhile the compression with modified RLE successfully compress all tested images with average compression ratio about 22.4 %.